OPINI AUDIT GOING CONCERN: SUATU KAJIAN EMPIRIS - Ardiani Ika Sulistyawati; Yulianti; Dian Triyani; Rr. Lulus Prapti Nugroho Setiasih Surjanti (SEAN Institute, 2023)
This research is motivated by the existence of problems in the form of gap phenomena in the form of discrepancies in the results of the analysis regarding the direction of the relationship between the independent variables of the study which include the previous year's audit opinion, company size, liquidity, profitability, and solvency with the dependent variable going concern audit opinion in manufacturing companies listed on the Stock Exchange Indonesian Securities in 2016- 2020. This study aims to examine the effect of the previous year's audit opinion, company size, liquidity, profitability, and solvency on going concern audit opinion in manufacturing companies listed on the Indonesia Stock Exchange. The research was conducted with a quantitative research approach. This type of research is descriptive research. The population in this research is 160 companies and the total sample is 32 manufacturing companies listed on the Indonesia Stock Exchange 2016-2020. The variables related to this research are the previous year's audit opinion, company size, liquidity, profitability, and solvency and going concern audit opinion in manufacturing companies. Data analysis technique using logistic regression. The results showed that there was a significant effect on the previous year's audit opinion, profitability, and solvency variables on going concern audit opinion in manufacturing companies, while the company size and liquidity variables had no significant effect on going concern audit opinion in manufacturing companies listed on the Stock Exchange. Indonesia.